The impact of the use of strategic planning on the development of retail trade in Saudi Arabia - Idris, Jafar Abdullah Mousa (Journal of Economic, Administrative and Legal Sciences, 2017)
The retail trade of the largest economic activities, and represent more than 40% of the total volume of employment in the world's projects and working up the hands that work in this area to 20% of total employment size ratio.The purpose of research is to identify the impact of strategic planning on the development of retail trade in Saudi Arabia, which is considered the first Arab in the retail of what is available to their human, physical and geographical potential.The study concluded that Rania is using province strategic planning in the development of retail tradeFind assumed that Rania province do not use strategic planning in retail development in Saudi Arabia, specifically province Rania.The researcher used data collection and analysis to the questionnaire and analyzed through a statistical program for Social Sciences (SPSS) researcher has used averages to determine the average Answers study sample all paragraphs. The study dealt with the basic concepts of strategic planning, retail trade, functions and retail trade in the Kingdom of Saudi Arabia.The study reached the most important results that Rania governorate has a distinct geographic location and is characterized by a distinguished commercial center. Retailing is somewhat booming compared to the past, but Rania does not use strategic planning to develop it. The study made recommendations to develop retail trade in the governorate and the entire Kingdom. The most important of which is the need to use the scientific foundations for strategic planning in the development of retail trade.
Keywords: strategic planning; retail trade; the province of Rani